Inflation and Financial Depth - Khan, Mohsin (IMF Working Papers; Working Paper ;, 2001)
There is now a substantial theoretical literature arguing that inflation impedes financial deepening. Furthermore, it has been hypothesized that the relationship is a nonlinear one, in that there is a threshold level of inflation below which inflation has a positive effect on financial depth, but above which the effect turns negative. Using a large cross-country sample, empirical support is found for the existence of such a threshold. The estimates indicate that the threshold level of inflation is generally between 3 and 6 percent a year, depending on the specific measure of financial depth that is used.